2021
DOI: 10.1126/science.abg8790
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule laser nanospectroscopy with micro–electron volt energy resolution

Abstract: Ways to characterize and control excited states at the single-molecule and atomic levels are needed to exploit excitation-triggered energy-conversion processes. Here, we present a single-molecule spectroscopic method with micro–electron volt energy and submolecular-spatial resolution using laser driving of nanocavity plasmons to induce molecular luminescence in scanning tunneling microscopy. This tunable and monochromatic nanoprobe allows state-selective characterization of the energy levels and linewidths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…These shifts may originate from several physical effects. Due to the presence of the STM tip generating external static and dynamic electrical fields, Stark and photonic Lamb effects may contribute to the observed energy shifts 18 , 45 – 48 . However, recent STML and photoluminescence works demonstrated that these effects may at best lead to few meV shifts of the emission maxima 18 , 48 , and cannot explain the large blue shifts reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These shifts may originate from several physical effects. Due to the presence of the STM tip generating external static and dynamic electrical fields, Stark and photonic Lamb effects may contribute to the observed energy shifts 18 , 45 – 48 . However, recent STML and photoluminescence works demonstrated that these effects may at best lead to few meV shifts of the emission maxima 18 , 48 , and cannot explain the large blue shifts reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the simulations we have neglected the finite temperature effect because the STM-PL experiments were efficiently performed only under cryogenic temperatures. 17 , 18 The vibrational integrals were computed with the DynaVib software. 62…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the TEFE spectra and images in Figure 2 were broadened with a full-width at half-maximum (fwhm) of 5.00 meV. For high-order vibrational transitions, a smaller fwhm of 0.50 meV, which has been obtained very recently in STM-based photoluminescence excitation spectroscopy, 18 was used to better locate the weak combinational transitions.…”
Section: Methodsmentioning
confidence: 99%
“… 131 Other examples based on other signals could be mentioned as well, such as single-molecule laser nanospectroscopy with micro-electron volt energy resolution. 132 Therefore, the importance of the future of optics in life sciences and its related technological impact was shown. 133 …”
Section: Perspectives Towards Biosensing and Single Molecule Detectio...mentioning
confidence: 99%